2018
DOI: 10.1089/thy.2017.0507
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Iodine Intake and Subclinical Hypothyroidism in Children and Adolescents Aged 6–19 Years: Results of the Sixth Korean National Health and Nutrition Examination Survey, 2013–2015

Abstract: Excess iodine was prevalent in Korean children and adolescents, and it may be associated with SCH. Therefore, monitoring the iodine status and education on adequate intake are needed in iodine-rich areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…Although UIC was statistically associated with levels of TSH and fT4 in the present study, no association was found between iodine status and incidence of thyroid dysfunction. Nevertheless, in a study performed by Kang et al [29] on children and adolescents, iodine excess was found to be associated with subclinical hypothyroidism. Iodine excess has also been reported to be associated with iodine-induced thyroid dysfunction and autoimmune thyroid diseases [30].…”
Section: Discussionmentioning
confidence: 97%
“…Although UIC was statistically associated with levels of TSH and fT4 in the present study, no association was found between iodine status and incidence of thyroid dysfunction. Nevertheless, in a study performed by Kang et al [29] on children and adolescents, iodine excess was found to be associated with subclinical hypothyroidism. Iodine excess has also been reported to be associated with iodine-induced thyroid dysfunction and autoimmune thyroid diseases [30].…”
Section: Discussionmentioning
confidence: 97%
“…World Health Organization (WHO) suggests that an adequate UIC should be between 100 and 200 μg/L, and an UIC in the range of 200-299 μg/L and >300 μg/L indicate more than adequate intake and the presence of excessive iodine, respectively (21). According to the criteria of iodine status above, there are a large percentage of persons with either iodine deficiency or excessive iodine (28,48,49). It has been clear that iodine deficiency can result in impaired production of thyroid hormones and thus cause adverse effects on human health.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding studies that did not fulfill the inclusion criteria, 185 candidate studies were further evaluated by reading full texts. Another 164 studies were further excluded and 21 studies from literature were eligible into meta-analysis (26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46). Therefore, a total of 22 studies (21 studies from literature and our cross-sectional study) were finally included.…”
Section: Dose-response Meta-analysismentioning
confidence: 99%
“…Excess iodine intakes in populations can result from diets that are naturally high in iodine and/or groundwater. In South Korea, the mUIC in SAC and adolescents is 449 µg/L, mainly due to high intakes of iodine-rich seaweed (25). Djibouti, on the Horn of Africa, has excess iodine intakes due to very high iodine in groundwater: the median iodine concentration in drinking water is 92 μg/L (IQR:37-158 μg/L) and the mUIC is 335 μg/L in SAC and 265 μg/L in pregnant women, despite only 1.6% of Djibouti salt samples being adequately iodized (>15 ppm) (26).…”
Section: Countries With Excessive Iodine Intakementioning
confidence: 99%